2021
DOI: 10.3390/cancers13081772
|View full text |Cite
|
Sign up to set email alerts
|

PGC1α Loss Promotes Lung Cancer Metastasis through Epithelial-Mesenchymal Transition

Abstract: PGC1α oppositely regulates cancer metastasis in melanoma, breast, and pancreatic cancer; however, little is known about its impact on lung cancer metastasis. Transcriptome and in vivo xenograft analysis show that a decreased PGC1α correlates with the epithelial–mesenchymal transition (EMT) and lung cancer metastasis. The deletion of a single Pgc1α allele in mice promotes bone metastasis of KrasG12D-driven lung cancer. Mechanistically, PGC1α predominantly activates ID1 expression, which interferes with TCF4-TWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…Previous studies have reported that the TGFβ1 signalling pathway promotes the interaction between TCF4 and TWIST1 and consequently upregulates the expression of EMT-related genes [ 16 ]. The interaction between TCF4 and TWIST1 was also confirmed in this study ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that the TGFβ1 signalling pathway promotes the interaction between TCF4 and TWIST1 and consequently upregulates the expression of EMT-related genes [ 16 ]. The interaction between TCF4 and TWIST1 was also confirmed in this study ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…PTHLH, which is encoded by parathyroid hormone-related protein (PTHrP), serves as an external stimulus to maintain bone turnover and skeletal homeostasis [ 14 ]. Previous studies have reported that PTHrP promotes the growth, metastasis, and chemoresistance of various cancers, such as lung, colorectal, prostate, pancreatic, and breast cancers [ 15 , 16 , 17 , 18 , 19 , 20 ]. A recent study reported that tumour-derived PTHrP causes cancer cachexia by promoting WAT browning and skeletal muscle loss [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To analyze the gene expression, quantitative PCR was performed using the SYBR Green PCR Master Mix (Applied Biosystems, Foster City, CA, USA) and LightCycler96 real-time PCR (Roche, Basel, Switzerland). Ct values were normalized to the human 36B4 gene and relative mRNA expression was calculated versus human 36B4 expression as previously described [ 36 ]. The primer sequences used in the experiment are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%